Cold burns as a result of cosmetic cryolipolysis: An emerging concern from the NSW Statewide Burn Injury Service. (January 2023) - Barry, Nick P.; Jackson, Shane R.; D'Jamirze, Alex; Gates, Robert J.; Maitz, Peter K.M.; Issler-Fisher, Andrea
Abstract: Cold burns are an uncommon mechanism of burn injury in Australia, where environmental exposure to freezing temperatures is rare. Aetiological research shows that most likely causes are related to intentional injury or industrial accidents 1 Cryolipolysis, a cosmetic technique advertised as 'fat freezing', has recently emerged as a method of fat reduction and body contouring. Whilst perceived as safe 4, 5, this study presents the world's first case series on cold burns sustained from cryolipolysis. A retrospective review was undertaken of the New South Wales Statewide Burn Injury Service (SBIS) Registry, a prospectively collected database of all patients treated by NSW burns units. Ten patients from 2012 to 2020 were identified who sustained cold burns as a direct complication of cosmetic cryolipolysis. Mean total body surface area (TBSA) injured was 1% (range 0.5–3%). Burn depth ranged from superficial to full thickness. Two patients required excision and split-thickness skin grafts. Mean time to complete healing was 10 days (range 7–13) for those patients with partial thickness injuries, and 38 days (range 32–45) for those who required skin grafts. This case series provides strong evidence that cyrolipolysis can cause cold burns leading to varying degrees of skin injury, even requiring skin grafts. These injuries should be classified as burns and referred to specialist burn centres for treatment. Further research is needed to determine the specific aspects of cryolipolysis cold burn risk, and practitioners trained to reduce this risk and include it in consent processes. The authors advocate for education and regulation to prevent such injuries, and challenge perceptions of the technique as a minor, risk-free cosmetic treatment.